(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The paper, within the tasks of social philosophy, deals with the problems of an extraordinary component of the phenomenon of health preservation – religious health-preserving practices. The author analyzes some fundamental health-preserving customs, the foundations of which are presented in the centuries-old traditions and dogmas of world religions. The paper focuses on the fact that the actualization of health-preserving religious practices in modern conditions occurs in the format of implementation of their transcendental meanings into popular wellness programs of the wellness industry. Investigating the evolution of the phenomenon of health preservation as a social phenomenon and its socio-philosophical understanding in the modern consumer society, the author comes to the conclusion that success in problem solving in healthcare directly depends on the qualitative and systematic cumulative use of various mutually complementary techniques for preserving health from scientific medicine, alternative and traditional medicine, as well as the application of religious health-preserving practices. From the view point of the author, health preservation is the art of strategic action, which presumes the unification of all potentially productive components, both at the state level and in the case of an individual inclination of a person to lead a healthy lifestyle. Therefore, it is advisable to further study the specifics of the interaction between religion and medicine in the field of existential issues, which deepens the understanding of the mechanisms of social determination and enables, especially on the preclinical stages, effective prevention of diseases. Key words: social philosophy, health preservation, world religions, wellness industry, consumer society, religious needs